Prevalence and Determinants of Caesarean Section in a Private Health Facility: A Cross-sectional Study (Bangladesh Pharmaceutical Journal, 2023)
Emergency obstetric care (EmOC) has dramatically lowered the maternal death rate in Bangladesh since the early 1990s. Rising caesarean section rates over the past ten years have had an impact on the nation's economy in addition to other signs of better mother care. According to demographic and health surveys, caesarean section rates increased from 3.5% in 2004 to 23% in 2014. Women who become pregnant after 35 years, live in cities, have a higher level of education and frequently use antenatal services have a greater average annual rate of prevalence in caesarean sections. The objective was to assess the indications and the trends of caesarean sections done over a two-month period. The study of prevalence and determinants of caesarean section was conducted in a renowned private hospital in Dhaka. Among 197 women who were admitted to the department of obstetrics and gynecology, the number of total deliveries was 175 (89% of total admission). The indications varied a little in cases of lower abdominal pain and preeclampsia. Antepartum hemorrhage (APH) and breech have a small proportion (about 5% both). The proportion of repeated caesarean sections was 47%. Recently the indication of a maternal choice is also coming up (11%). The data were compared and analyzed to determine if the indications were significant enough for cesarean delivery. Although a caesarean section is currently a relatively safe obstetrical procedure, it is advised that the indications should be carefully evaluated in order to lower caesarean section rates.Bangladesh Pharmaceutical Journal 26(2): 195-203, 2023 (July)